Suicidal ideation in the elderly: Psychological analysis (Research, Society and Development, 2022)
Objective: to describe the main aspects related to suicidal ideation in the elderly, identifying the activities developed by the psychologist. Data collection took place on the VHL (Virtual Health Library) and SCIELO (ScientificElectronic Library Online) platforms. Methodology: descriptive, exploratory, qualitative, review type VHL (Virtual Health Library) and SCIELO (ScientificElectronic Library Online). Results: group interventions prove to be effective with space for listening, recognition, legitimation and support for families in psychological distress. It is necessary to avoid the perpetuation of value judgments, creating a sphere of reception and security in the psychologist's conduct. Conclusion: suicidal ideation in the elderly is the result of a complex network of biological, psychological, social, cultural and environmental factors, therefore, the therapeutic approach must also be broad, in order to provide the elderly with coping mechanisms.